Cloning, nucleotide sequencing, and expression of an opine dehydrogenase gene from Arthrobacter sp. strain 1C. - Dairi, T (1995)
The gene coding for opine dehydrogenase from Arthrobacter sp. strain 1C was cloned onto plasmid pBluescript KS(-), and the nucleotide sequence of the 1,077-bp open reading frame consisting of 359 codons was identified as the odh gene. Transformed Escherichia coli cells overproduced NAD+-dependent opine dehydrogenase under control of the promoter of the lac gene on pBluescript KS(-).